THE RS11792633-T ALLELE OF IL-33 GENE IS ASSOCIATED WITH SYSTEMIC SCLEROSIS - Koca, S. S.; Pehlivan, Y.; Kara, M.; Oner, F. A.; Yilmaz, N.; Cetin, G. Y.; Onat, A. M. (Bmj Publishing Group, 2013)
[Abstract Not Available]
Keywords: Involvement